(untitled) (Szociológiai Szemle, 2024)
On the basis of a survey on antisemitism among Hungarian college and university students conducted on a nationwide representative sample of 1000 students the author estimates that 7 percent of the students form a group of hard-core anti-semitic while 43 percent of the students are free of all forms of antisemitism. In the present article he investigates the strength of latency in the group and finds that only a small proportion of the interviewees measurement should not be substantially corrected by the proportion of latent anti-semitic. In the second part of the article the author measures the proportion of students who could be the avant-garde of political antisemitism in the future elite.